"Division at Home, Unity Abroad? The Impact of Local and International Dynamics on Political Opportunity Structure in the Territorio Indígena y Parque Nacional Isiboro Secure Highway Conflict". Issue 3 (August 2022) - Buice, Melissa
This article observes developments in the construction of a controversial highway project through the protected TIPNIS territory in Bolivia's Amazonian region between 2003 and 2021. The case study uses theories of political opportunity structure to guide the qualitative investigation about how indigenous groups confronted uncertain domestic and international institutional conditions. To confront divisive obstacles at home, activists ultimately developed strategies for operating within the formal rules and institutions while also creating their own "alternate" or informal sites of contestation at the international and domestic levels. This article ends with a discussion of the significance and power of these alternative institutions to influence policy.